Requisitos para inscripción del registro sanitario de dispositivos médicos de entidad reguladora DIGEMID y autoridades reguladoras nacionales de referencia regional - Villanueva Sedano, Lucy Carmen (2019)
The objective of this study was to determine similarities and differences in the requirements for the registration of medical devices of the regulatory entity DIGEMID and the national regulatory authorities of reference (INVIMA, ANMAT, ANVISA, CECMED, COFEPRIS), for which proceeded to perform the bibliographic search, and obtained the results presented in comparative tables between the regulatory entity of Peru and each of the national regulatory authorities of reference considered for the study. The results showed that the requirements requested by DIGEMID for the registration of sanitary registration of medical devices in Peru are similar to the national regulatory authorities of reference; However, INVIMA, ANMAT, ANVISA, CECMED, COFEPRIS present requirements with greater rigor and emphasis on the safety aspect of medical devices when requesting different tests, studies, tests, reports on the safety and efficacy of the devices to be registered, in comparison to Peru where the requirements that detail and dictate guidelines to follow regarding safety are not explicit. It is concluded that the General Directorate of Drugs, Supplies and Drugs (DIGEMID) has requirements similar to ANMAT; however, the ANMAT has more requirements regarding the safety of medical devices, the requirements requested by ANVISA are smaller and simpler compared to the DIGEMID, INVIMA has the same number of requirements and resemblance to DIGEMID, the the requirements requested by CECMED are greater and more rigorous in terms of safety and effectiveness for moderate risk, high risk and critical risk class devices compared to DIGEMID and COFEPRIS has requirements that are more detailed in the area of safety, security, efficiency compared to DIGEMID